INFANTILE HEMANGIOMA IN THE GLUTEAL REGION (International Journal of Scientific Research and Management (IJSRM), 2025)
This case report describes the management of an infantile hemangioma (IH) in a 5-year-old child, diagnosed prenatally as an amorphous mass located in the right gluteal region. Over the child’s first five years, the vascular lesion progressively infiltrated adjacent soft tissues, compromising the functionality of the affected area. Despite initial treatment with propranolol, the patient showed a limited response, with lesion progression and associated symptoms. Due to the therapeutic ineffectiveness of the medication, surgical resection was chosen as the primary approach. The macrocystic lesion, with multiple loculations measuring approximately 10x4x7 cm, was removed without adverse complications. This case underscores the importance of early diagnosis and appropriate management of infantile hemangiomas, highlighting the surgical approach over the first-line treatment with propranolol in cases where initial treatment does not yield satisfactory results, especially in situations posing functional risks. The patient’s favorable outcome adds to the existing literature on the therapeutic outcomes of this approach.